Clinical Supervision: Teacher Professionalism and Performance - Luthfia Azzahra; Aghnesia Rahmy; Ilma Ridhona; Bagus Yanto (Foundation of Jannatun Naim Lampung, 2025)
This research describes how clinical supervision supports professionalism in teachers' performance. Clinical supervision is crucial in developing teachers' teaching skills and competencies through continuous observation, feedback, and reflection. This study employs a qualitative descriptive approach with a sample of two teachers from SMAN 4 Kotabumi, each with different experience levels. Data collection techniques were conducted through observations using an interview sheet as the instrument. Clinical supervision positively impacts teachers' performance, enhancing discipline, commitment, and classroom management skills. Senior teachers performed better in planning and implementing lessons, while novice teachers still required further guidance to improve teaching quality. Clinical supervision has proven to be effective in enhancing teacher professionalism and performance.